The Effects of Ocean Surface Waves on Tropical Cyclone Intensity: Numerical Simulations Using a Regional Atmosphere‐Ocean‐Wave Coupled Model. Issue 11 (15th November 2022) - Zhao, Biao; Wang, Guansuo; Zhang, Jun A.; Liu, Li; Liu, Jiping; Xu, Jing; Yu, Hao; Zhao, Chang; Yu, Xinzhu; Sun, Chao; Qiao, Fangli
Abstract: Tropical cyclones (TCs), especially landfalling intense storms often pose serious threats to life and property in coastal areas. Although TC track forecast skill has been improved in the past decades, the progress of advancing the intensity forecast lags that of the track forecast. One possible limiting factor is the absence of ocean surface waves in forecast systems. To better represent the interaction of TC and underlying ocean, a regional atmosphere‐ocean‐wave coupled model is employed in this study. Twenty‐one TCs of a whole year in 2013 are retrospectively simulated through twin simulations, a Control and a Fully coupled run. Results show that TC intensity bias has been significantly reduced in the fully coupled simulation, in which five ocean surface wave related physical processes are considered, including wave modulation of momentum flux, sea spray effect on enthalpy flux, surface current and Stokes drift on air sea flux, non‐breaking wave induced mixing in the upper ocean as well as rain induced ocean surface cooling. A case study approach is used to diagnose the effect of individual surface wave related physical process on TC simulations. Similar to the effect of sea spray, surface waves also act as positive feedback on TC intensification by modulating air‐sea momentum flux. Absolute angular momentum budget analysis suggests that larger radial inflows and stronger updrafts near the eyewall promote the radial and vertical advections of absolute angular momentum and in turn lead to a stronger TC in Fully coupled simulation. The TC structure and size agree better with observations in Fully coupled simulation. Plain Language Summary: Ocean surface waves, have been widely acknowledged to modulate the flux exchange at air‐sea interface. Their influence on multiscale air‐sea processes, especially tropical cyclone, has attracted much attention in recent years. However, most of the studies usually focused on TC case study. To quantify the effects of ocean surface waves on tropical cyclone evolution. This study uses a regional atmosphere‐ocean‐wave coupled model to conduct retrospective simulations of all 21 tropical cyclones passing through the model domain in 2013. Results show that ocean surface waves play an important role in TC intensity and structure. Surface waves enhance the simulated inflow in the boundary layer that leads to more radial momentum transport and stronger updrafts near the eyewall region. These processes together help enhance the storm intensity and reduce the biases of intensity forecasts. The findings of this research emphasize the importance of ocean surface waves for TC studies and forecasts. Key Points: Surface waves lead to significant reduction of intensity bias and improvement of simulated TC size The modulation of air‐sea momentum flux by surface waves acts as positive feedback on TC intensification The enhanced air‐sea fluxes by surface waves help increase the angular momentum convergence, leading to improved representation of TC structure